2019
DOI: 10.1186/s12938-019-0676-8
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate relationship between the kinematic and clinical parameters of knee osteoarthritis population

Abstract: Background Biomechanical and clinical parameters contribute very closely to functional evaluations of the knee joint. To better understand knee osteoarthritis joint function, the association between a set of knee biomechanical data and a set of clinical parameters of an osteoarthritis population (OA) is investigated in this study. Methods The biomechanical data used here are a set of characteristics derived from 3D knee kinematic patterns: flexion/extension, abduction/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Patient improvement was determined based on the KOOS questionnaire. Based on a literature review and a preliminary study [21], the KOOS pain subscale was identified as the most representative score and therefore its variation between baseline and 6 months was used to determine whether a patient's condition improved (Class I) or not (Class nI). A growing consensus in the knee OA literature suggests that identifying a single threshold to define a meaningful change in the KOOS pain score across varying OA severity and followup periods is problematic [22,23].…”
Section: Identification Of Patients According To the Improvement In Tmentioning
confidence: 99%
“…Patient improvement was determined based on the KOOS questionnaire. Based on a literature review and a preliminary study [21], the KOOS pain subscale was identified as the most representative score and therefore its variation between baseline and 6 months was used to determine whether a patient's condition improved (Class I) or not (Class nI). A growing consensus in the knee OA literature suggests that identifying a single threshold to define a meaningful change in the KOOS pain score across varying OA severity and followup periods is problematic [22,23].…”
Section: Identification Of Patients According To the Improvement In Tmentioning
confidence: 99%
“…Only a few studies on gait in hip OA reported data for the ankle or knee. Of these, some reported no significant differences in knee ROM [ 6 ], while others described a reduction in knee flexion ROM [ 22 , 27 , 36 , 40 , 44 , 45 ] and greater [ 6 , 22 , 45 ] or comparable [ 27 ] peak ankle dorsiflexion in the affected leg in patients with hip OA compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of correlation between kinematic features of gait waveform data and clinical parameters has been, basically, done using a univariate correlation analysis [9][10][11][12]. The later investigate the relationship between a pair of two variables individually, which could occult important correlation as shown in our previous study [16]. CCA belongs to the family of exploratory analysis and allows investigation of the (simultaneous) relationship between two sets of variables.…”
Section: Clustersmentioning
confidence: 99%
“…3 of 13 observed on the same individual. The CCA is currently used in some disciplines such as ecology [18,19], biology [20,21], hydrology [22,23], and health [16].…”
Section: Introductionmentioning
confidence: 99%